Enhancing English Writing Skills Through Reciprocal Social Media Messaging Tasks in The EFL Classrooms - Iswahyuni, Dwi; Sari, Angela Bayu Pertama; Rejeki, Sri; Yogyanti, Devita Widyaningtyas (PROJECT (Professional Journal of English Education), 2026)
Social media has increasingly been incorporated into classroom activities in the digital era, including for teaching English as a foreign language. This study investigates the integration of reciprocal social media messaging tasks into an EFL classroom. This study aimed to find out whether reciprocal social media messaging tasks could enhance students’ writing skills and in what ways this method contributed to the enhancement of their writing skills. Reciprocal social media messaging tasks involved students exchanging messages back and forth and responding to each other. Moreover, the topic of the tasks in this study was invitations which led to informal writing. Furthermore, this study was a qualitative study that employed questionnaires and observations as the research instruments. The results showed that reciprocal social media messaging tasks could enhance EFL students’ English writing skill. In addition, this method could contribute to the enhancement of several writing aspects, such as vocabulary development, interactive writing, pragmatic competence, functional writing skills, spelling and grammar in real context, as well as coherence and message clarity. Reciprocal social media messaging tasks improved student engagement, writing performance, and awareness of language use in a more authentic, digital environment.